Hal Koch og Grundtvig - Fabricius Møller, Jes (Historisk Tidsskrift, 2013)
Hal Koch and Grundtvig Hal Koch (1904-1963), Danish theologian and professor of Church History at the University of Copenhagen, was despite his rapid rise in the academic world relatively unknown to the broader population in 1940 when he invited the public to a series of lectures on the renowned nineteenth century theologian, politician, author, historian, and inspirer of the Danish folk high school movement, N. F. S. Grundtvig (1783-1872). Interest in Grundtvig, which had been dwindling during the inter-war period, had suddenly experienced a renaissance in the wake of national feelings evoked by the German occupation. Koch's interest in Grundtvig was also new. His lectures called for national self-consciousness, an awareness of being Danish and Christian as a common rallying point. His words were solemn and stirring. At that time most of the Danish youth organizations had joined together in establishing the Danish Youth League (Dansk Ungdomssamvirke) to mobilize youth around a broad national and definitely non-political program based on the principles of democracy. They picked Hal Koch as their leader, since the views he expressed in his lectures on Grundtvig accorded extensively with the working principles of the League. In the meantime Koch changed his position. Representatives of the League were practically left in a state of shock when on 20 November 1940 he presented them for the first time with his program, which was highly political. National sentiment was replaced with political education. The young were to be brought up as good democrats. What caused Koch to change his attitude will have to be dealt with in depth by his biographer. It is likely, though, that he changed his mind, because he feared an upsurge of national sentiment might easily turn into something comparable to nazism. In this respect his thinking developed ideas on Danish democracy and culture expressed by two other contemporary historians, both prominent politicians, Peter Munch (Social Liberal Party) and Hartvig Frisch (Social Democratic Party). Koch gradually abandoned the Grundtvigianism he had propounded in 1939-1940. He continued to cite Grundtvig and recognized his historical significance, but he found in Grundtvig no contemporary legitimation of either democracy or the folk high school that he founded at Krogerup after the war. As headmaster of the folk high school Koch found himself at odds with broad segments of the agricultural population, and in 1950 he unleashed a severe criticism of Grundtvig and Grundtvigianism. His attack was strongly inspired by the thinking of the recently deceased Danish historian of religion, Vilhelm Grønbech. Krogerup met a storm of opposition, but at length it became the norm for running a folk high school for the youth of modern, urbanized Denmark. Translated by Michael Wolfe